Sub-toxic cisplatin concentrations induce extensive chromosomal, nuclear and nucleolar abnormalities associated with high malignancy before acquired resistance develops: Implications for clinical caution. - John G Delinassios; Robert M Hoffman; George Koumakis; Dimitrios Palitskaris; Kyriaki-Nefelli Poulatsidou; George J Delinasios (PLoS ONE)
Aim This study investigates the impact of sub-toxic cisplatin levels on nuclear and nucleolar abnormalities and chromosome instability in HeLa cells since our current knowledge of cisplatin effects on these parameters is based on studies with high concentrations of cisplatin. Materials and methods HeLa cells were exposed to gradually increasing sub-toxic doses of cisplatin (0.01 to 0.2 μg/ml). Cells treated with 0.1 and 0.2 μg/ml, termed HeLaC0.1 and HeLaC0.2, were not cisplatin-resistant, only exhibiting a slightly reduced viability, and were termed "cisplatin-sensitized cells." Giemsa and silver staining were used to detect nuclear and nucleolar abnormalities and chromosomal alterations. Results Notable abnormalities were observed in HeLaC0.1 and HeLaC0.2 cells after treatment with sub-toxic concentrations of cisplatin: nuclei showed abnormal shapes, blebs, micronuclei, fragmentation, pulverization, and multinucleation; nucleoli exhibited irregular shapes and increased numbers; anaphase cells showed more nucleolar organizing regions. Abnormal chromosome segregation, heightened aneuploidy (81-140 chromosomes), polyploidy, double minutes, dicentrics, chromatid exchanges, chromatid separations, pulverization, and chromosome markers were prominently noted. These abnormalities were intensified in cells pre-sensitized to 0.02 or 0.08 μg/ml cisplatin for seven days, then exposed to 0.03 or 0.1 μg/ml cisplatin for 24 hours, and finally cultured in cisplatin-free medium for 24 hours before chromosome analysis. Conclusion HeLa cells subjected to increasing concentrations of sub-toxic cisplatin exhibited large-scale, multiple-type abnormalities in nuclei, nucleoli, chromosomes, and chromosomal numbers, indicating genetic/chromosomal instability associated with high malignancy, before the development of cisplatin resistance. These results suggest that low doses of cisplatin administration in the clinical setting may promote malignancy and caution should be used with this type of treatment.